The Experiment of Floating Ability of Material of Polyurethane and Styrofoam - Indradi Setiyanto; Agus Hartoko (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2006)
Polyurethane can be used as alternative of substituted material of synthetic cork (Styrofoam) giving buoyancy at float vest. The research was aimed to observe the difference both materials (Polyurethane and cork) on acceptable load, so that efficiency can be estimated. The same load was given to gravity at both material that is 234.576 g, then checked the float ability. Results showed that Polyurethane indicated buoyancy of polyurethane better cork, with efficiency 3.6 %, for sample material with size of 10 cm x 7.5 cm x 5.5 cm. The Significant change of efficiency was expected can be done by determination of material (sample) according to use in field and different density of polyurethane when conducting moldings process. Key words: The experiment of floating ability